Dynamic anticounterfeiting and tunable lasing with screen-printed cholesteric liquid crystal elastomers - Guangyin Qu; Lulu Guo; Xiaojuan Zhang; Siqi Li; Yan Kuai; Weiwei Fu; Tianyu Yang; Jialin Wen; Benli Yu; Zhijia Hu (Proceedings of the National Academy of Sciences, 2026)
Structural colors hold significant application value in anticounterfeiting, displays, and smart coatings due to their high stability, eco-friendliness, and dynamic optical response potential. However, conventional fabrication strategies for photonic crystals—such as photolithography and inkjet printing—suffer from limitations including high mask costs, nozzle clogging, lattice defects, and difficulties in scaling production. This study introduces an innovative screen-printing technique to achieve high-fidelity and multicolor structural color patterning based on cholesteric liquid crystal elastomers (CLCEs), overcoming key challenges in controlling the alignment of mesoscopic helical structures and ensuring spatial homogeneity of the photonic bandgap. Crucially, the chiral helical superstructure of CLCEs was investigated, revealing its decisive role in governing the circular polarization properties of the reflected light. The printed patterns exhibit dynamic optical behaviors, including viewing-angle-dependent color shifts, inherent selective circularly polarized reflection dictated by the handedness of the helix, and reversible mechanochromic responses under strain. Furthermore, integration of photochromic spiropyran enables multistimulus-responsive color and fluorescence switching under light and thermal stimuli, as well as ultraviolet-tunable (645 to 685 nm) random lasing emission. This work demonstrates that screen-printed CLCEs, with their excellent substrate compatibility and scalability, constitute a promising platform for next-generation anticounterfeiting labels, smart packaging, and flexible photonic devices.